Recent progress in tackling Zn anode challenges for Zn ion batteries. Issue 46 (17th November 2021) - Hu, Wei; Ju, Jingge; Deng, Nanping; Liu, Mengyao; Liu, Weicui; Zhang, Yixuan; Fan, Lanlan; Kang, Weimin; Cheng, Bowen
Abstract : Recent process in tackling Zn anode challenges is summarized, including designing anode structure, modifying electrolyte, optimizing separator and developing polymer electrolytes, which present a reference for constructing high-performance ZIBs. Abstract : The growing demand for safer electrical energy storage has stimulated the pursuit of alternative advanced batteries. Aqueous Zn ion batteries (ZIBs) are receiving increasing attention due to their high safety, low cost, and environmental friendliness. However, the long-standing issues of low coulombic efficiency (CE) and poor cycle life of Zn anodes, influenced by dendrites and side reactions (hydrogen evolution and corrosion), have seriously hindered their practical application. Here, we begin with issues encountered by Zn metal in aqueous electrolytes (dendrites, hydrogen evolution and corrosion) and analyze its formation processes and mechanisms. Then, recent advances in advanced material and structural designs based on different battery components to suppress Zn dendrites and side reactions are summarized in detail, including designing anode structures, modifying the electrolyte, optimizing the separator and developing polymer electrolytes. Finally, opinions on current challenges and perspectives on future research directions are provided.